1999
DOI: 10.1677/joe.0.1600103
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between oestradiol and glucocorticoid regulatory effects on liver-specific glucocorticoid-inducible genes: possible evidence for a role of hepatic 11beta-hydroxysteroid dehydrogenase type 1

Abstract: In vitro, 11 -hydroxysteroid dehydrogenase type 1 (11 -HSD-1) catalyses the interconversion of active corticosterone and inert 11-dehydrocorticosterone. 11 -HSD-1 is highly expressed in liver, where the reaction direction is 11 -reduction, thus potentially increasing intrahepatic active glucocorticoid levels. Inhibition of 11 -HSD-1 increases insulin sensitivity in humans in vivo suggesting that hepatic 11 -HSD-1 plays a role in the maintenance or control of key glucocorticoid-regulated metabolic functions.We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Oestrogen treatment of ob/ob mice decreased the activity and expression of hepatic glucose-6-phosphatase, contributing to normalisation of blood glucose levels [27]. Furthermore, estrogen treatment of rats significantly decreased the hepatic activity and expression of 11β-hydroxysteroid dehydrogenase type 1, an enzyme that catalyses the conversion of inactive 11-dehydrocorticosterone to corticosterone [28].…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen treatment of ob/ob mice decreased the activity and expression of hepatic glucose-6-phosphatase, contributing to normalisation of blood glucose levels [27]. Furthermore, estrogen treatment of rats significantly decreased the hepatic activity and expression of 11β-hydroxysteroid dehydrogenase type 1, an enzyme that catalyses the conversion of inactive 11-dehydrocorticosterone to corticosterone [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, the expression and activity of 11b-HSD1 is increased in male rats compared with female rats, 40 and estrogen treatment represses hepatic 11b-HSD1 mRNA expression and activity in rodents. 41,20 Whole-body 11b-reductase activity, which primarily reflects hepatic 11b-HSD1activity, is higher in men than in women, [42][43][44] suggesting a genderspecific regulation also in humans. Lean women have lower 11b-HSD1 expression in adipose tissue than lean men; however, this gender-specific difference disappears in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have been shown to oppose the actions of insulin in the liver by upregulating expression of the rate-limiting enzyme PEPCK (Low et al 1994). Oestradiol, only in the presence of glucocorticoids, also downregulates expression of PEPCK (Jamieson et al 1999). Morton et al (2001) and others have shown that 11 -HSD1-null mice have increased hepatic insulin sensitivity, and increased glycaemic control for similar insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal infusion of glucocorticoid and oestradiol have been found to stimulate 11 -HSD1 mRNA expression and enzyme activity (Wang et al 1997, Sloboda et al 2001. In contrast, other researchers reported that infusion of dexamethasone (a synthetic glucocorticoid) and oestradiol decreased hepatic 11 -HSD1 mRNA and reductase activity in the male rat (Jamieson et al 1999, Nwe et al 2000. Thus the separate effects of cortisol and oestradiol on hepatic 11 -HSD1 and GR in the late-gestation sheep fetus remain unclear.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation